Velocity-Dependent Effect on the Peak Shear Strength of Rock Joints Considering the Distribution Characteristics of Contact Joint Surface - Ban, L.; Du, W.; Zheng, D.; Hou, Y.; Qi, C.; Yu, J.; Zhu, C.; Lu, Chunsheng (2024)
This study aims to elucidate the mechanism of velocity-dependent peak shear strength (PSS) for rock joints by examining the three-dimensional distribution characteristics of actual contact joint surface. Shear tests are conducted on saw-cut joints (SCJs) and natural rough rock joints under varying shear velocities (v) but a constant normal stress. The test results reveal that the PSS of SCJs decreases with increasing shear velocity, whereas the PSS of rough joints increases with v. Through analysis of the impact of v on the contact area, a PSS model is developed. The model demonstrates that for SCJs, the contact area decreases with increasing v, resulting in a reduction in the basic friction angle. Conversely, for rough joints, the contact area decreases with increasing v. However, it is observed that, considering the distribution characteristics of the apparent dip angle of asperities on the joint surface, the average roughness of joint surface increases as the contact area decreases. It is the increase in roughness that subsequently leads to an increase in the PSS of rock joints. The new model incorporates the influence of v on both the basic friction angle and peak dilation angle, and the interplay between these factors determines the PSS of rock joints.